SH2B3 (LNK) mutations from myeloproliferative neoplasms patients have mild loss of function against wild type JAK2 and JAK2 V617F. (17th April 2013) - Koren‐Michowitz, Maya; Gery, Sigal; Tabayashi, Takayuki; Lin, Dechen; Alvarez, Rocio; Nagler, Arnon; Koeffler, H. Phillip
Summary Somatic point mutations in the PH domain of SH2B3 (LNK), an adaptor protein that is highly expressed in haematopoietic cells, were recently described in patients with myeloproliferative neoplasms. We studied the effect of these mutations on the JAK2 signalling pathway in cells expressing either wild type JAK2 or the JAK2 V617F mutation. Compared to wild type SH2B3, PH domain mutants have mild loss of function, with no evidence for a dominant‐negative effect. Mutants retain binding capacity for JAK2, an established SH2B3 target, as well as for the adaptor proteins 14‐3‐3 and CBL. Our data suggest that the loss of SH2B3 inhibitory function conferred by the PH domain mutations is mild and may collaborate with JAK2 V617F and CBL mutations in order to promote either the development or the progression of myeloproliferative neoplasms.